Compound Danshen Dripping Pills Prevented Leptin Deficiency-Induced Hepatic ER Stress, Stimulated Autophagy, and Improved Insulin Resistance of ob/ob Mice. (3rd July 2020) - Shi, Yanan; Liu, Dan; Yuan, Jihong; Yan, Lihui; Zhan, Zhenfeng; Pan, Da; Lin, Laixiang; Mu, Biao
Abstract : Compound Danshen dripping pills (CDDP) is widely used for the treatment of coronary arteriosclerosis and ischemic heart diseases for decades of years. In our study, we interestingly discovered the effects and mechanism of CDDP on insulin resistance that increase the risk factor of cardiovascular diseases. Effects of CDDP on fasting blood glucose, the insulin tolerance test (ITT), the oral glucose tolerance test (OGTT), hepatic function, and underlying mechanism were analyzed in ob/ob mice. CDDP was found improving the impaired insulin signal sensitivity of ob/ob mice by ameliorating insulin and glucose tolerance, improving hepatic phosphorylation of the insulin receptor substrate-1 on Ser 307 (pIRS1) of ob/ob mice, and restoring hepatic function by decreasing serum ALT and AST, which increased in ob/ob mice serum. Decreasing hepatic phosphorylation of pancreatic ER kinase (PERK) and inositol-requiring enzyme-1 (IRE1) regulating hepatic ER stress in the liver of ob/ob mice were increased by CDDP. Furthermore, CDDP was also found stimulating ob/ob mice hepatic autophagy by increasing the expression of Beclin1 and LC3B, while decreasing P62 expression. Our study discovered an important role of CDDP on improving ob/ob mice insulin resistance and liver function probably through relieving hepatic ER stress and stimulating hepatic autophagy, which would broaden the application value and provide more benefits for treating cardiovascular patients. This trial is registered with NCT01659580 .